Student’s Spiritual Well-Being in Juveniles Prison in Indonesia: A Descriptive Study - Wahyu Saefudin; Sriwiyanti (Proceeding International Conference on Religion, Science and Education, 2023)
The high adolescent delinquency rate impacts many juvenile offenders who must undergo rehabilitation in juvenile prisons. The majority of perpetrators of crimes are teenagers. In Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, juvenile offenders have the right to receive public education and kesetaraan education. However, the rehabilitation process that was undertaken caused various psychological conditions, including stress, depression, anxiety, and difficulty adapting. These various psychological conditions make it difficult for children to complete their education correctly and cannot adapt to participating in the rehabilitation programs provided. According to the existing conditions, juveniles need a high level of spiritual well-being to overcome the various psychological problems they are experiencing. This study aims to determine the spiritual well-being level of students in 7 correctional facilities in Indonesia, including Sungai Raya Correctional Facilities, Tangerang, Manokwari, Karang Asem, Samarinda, Jakarta, and Mataram. The number of samples in this study was 100 juveniles obtained through a proportional random sampling technique. Data was collected using a spiritual well-being questionnaire consisting of 20 questions. The data were analyzed using descriptive analysis with SPSS 25 software. The research results indicate that most students have spiritual well-being in the moderate category at 43%, followed by the high category at 40% and the low category at 17%. Moderate spiritual well-being means juveniles have adequate resilience, internal peace, solidarity, harmony, and a close relationship with themselves, society, the Creator, and the environment. The study results will assist the Directorate General of Corrections in maintaining a high level of spiritual well-being and developing a coaching program that aims to increase the moderate and low levels of the spiritual well-being of students. Furthermore, a correctional facility, which is a place for juveniles to undergo rehabilitation programs, can organize training to increase the level of spiritual well-being in students.